Highly elongated vertical GaN nanorod arrays on Si substrates with an AlN seed layer by pulsed-mode metal–organic vapor deposition. Issue 9 (19th January 2016) - Bae, Si-Young; Jung, Byung Oh; Lekhal, Kaddour; Kim, Sang Yun; Lee, Jeong Yong; Lee, Dong-Seon; Deki, Manato; Honda, Yoshio; Amano, Hiroshi
Abstract : Precisely controlled morphology of GaN nanorods was obtained on a thin AlN seed layer and their height increased as the diameter of the mask openings decreased. Abstract : To extend the availability of nanostructure-based optoelectronic applications, vertically elongated nanorods with precisely controlled morphology are required. For group III nitrides, pulsed-mode growth has recently been reported as an effective method for growing nanorod arrays with geometric precision. Here, we demonstrated the growth of arrays of highly elongated nanorods on Si substrates by metal–organic chemical vapor deposition using a pulsed-mode approach. Unlike the thick and high (or middle)-quality GaN templates normally used, nanorod growth was performed on an ultrathin and low-quality AlN/Si platform. Using kinetically controlled growth conditions and a patterning process, exceptionally long GaN nanorods were achieved with high geometric precision. The grown nanorods showed considerably improved optical and structural properties while remaining in uniform arrays. This approach can be used with a variety of materials to obtain nanorods with high quality, high uniformity, and high aspect ratio, and it can also serve as an effective fabrication method for InAlGaN-alloyed core/shell nanostructures for optoelectronic nanodevices with ultrahigh efficiency.